Tracing the Origin of Groundwater Nitrate in an Area Affected by Acid Rain Using Dual Isotopic Composition of Nitrate. (29th November 2019) - Huang, Tianming; Li, Zhenbin; Ma, Baoqiang; Long, Yin
Abstract : Acid rain with a relatively high concentration of ammonium and nitrate can accelerate rock weathering. However, its impact on groundwater nitrate is uncertain. This study evaluated the dual isotopic composition of nitrate ( δ 15 N-NO3 - and δ 18 O-NO3 - ) from precipitation to groundwater in a rural mountainous area affected by acid rain. The average concentration for NH4 + is 1.25 mg/L and NO3 - is 2.59 mg/L of acid rain. Groundwater NO3 - concentrations ranged from <0.05 to 11.8 mg/L (baseline), and NH4 + concentrations ranged from 0.06 to 0.28 mg/L. The results show that groundwater δ 18 O-NO3 - values (-4.7‰ to +4.2‰) were lower than the values of rainfall δ 18 O-NO3 - (+24.9‰ to +67.3‰), suggesting that rainfall NO3 - contributes little to groundwater NO3 - . Groundwater δ 15 N-NO3 - values (+0.1‰ to +7.5‰) were higher than the values of δ 15 N-NO3 - derived from the nitrification of rainfall NH4 + (less than -4.7‰ in the study area), suggesting that nitrification of rainfall NH4 + also contributes little to groundwater NO3 - . This implies that rainfall NO3 - and NH4 + have been utilized. The dual isotopic composition of nitrate shows that baseline groundwater NO3 - is derived mainly from nitrification of soil nitrogen. The denitrification process is limited in the groundwater system. This study shows that the rainfall NO3 - and NH4 + contribute little to groundwater NO3 -, improving the understanding of the nitrogen cycle in areas with a high concentration of NH4 + and NO3 - in rainfall.